Application Software Maintenance Process : A Comparative Study - Suhana, Saidin (2004)
In the early study of software maintenance, Canning (1972) is considered maintenance as an iceberg where maintainer saw maintenance as narrow as correcting errors and as broad as expending and extending software functionality. This study is focusing the maintenance process of application software. Academic and Record Student Information System (ASIS) and Library Information System (LINTAS) are compared to differentiate the maintenance process between in house and vendor application. Maintenance process involved in ASIS is for emergency case and normal case. There two types of maintenance involve in ASIS, corrective and perfective. LINTAS, there three types of maintenance involve, adaptive, corrective and perfective. All the problems occur in LINTAS was sorted and solved via the vendor according to the contract.